2004
DOI: 10.1093/carcin/bgh274
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle kinase inhibitor expression and hypoxia-induced cell cycle arrest in human cancer cell lines

Abstract: Flow cytometric analysis of fibroblasts, normal breast epithelial cells and breast or other cancer cell lines identified variation in the abilities of cell lines to undergo cell cycle arrest as a response to hypoxia. Human mammary epithelial cells (HMEC), normal fibroblasts (Hs68 and WI38), HeLa cervical carcinoma and HTB-30 breast carcinoma cells arrest in G(1)/S in response to severe hypoxia. Hep3B hepatocellular carcinoma cells did not exhibit orderly G(1)/S arrest in response to severe hypoxia. We found a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
46
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 62 publications
11
46
1
Order By: Relevance
“…2). These results together with the observation that hypoxia induces G 1 arrest in various cancer cells (41,42) suggest that a considerable population of cells in the metastatic foci in vivo may be under G 1 arrest presumably because of insufficient nutritional states and/or relatively low O 2 concentrations (17). Considering that most of anticancer chemotherapeutic agents target cells in S or G 2 -M phases, rendering tumor cells under G 1 phase highly active in glycolysis and proliferative may cause increasing sensitivity to drugs by passing these cells through the metabolic checkpoint to undergo S and G 2 -M phases.…”
Section: Discussionsupporting
confidence: 69%
“…2). These results together with the observation that hypoxia induces G 1 arrest in various cancer cells (41,42) suggest that a considerable population of cells in the metastatic foci in vivo may be under G 1 arrest presumably because of insufficient nutritional states and/or relatively low O 2 concentrations (17). Considering that most of anticancer chemotherapeutic agents target cells in S or G 2 -M phases, rendering tumor cells under G 1 phase highly active in glycolysis and proliferative may cause increasing sensitivity to drugs by passing these cells through the metabolic checkpoint to undergo S and G 2 -M phases.…”
Section: Discussionsupporting
confidence: 69%
“…The second mechanism relies on sequestration of c-Myc and subsequent induction of the cell-cycle inhibitors p21 and p27 (33). The mechanism by which certain cancer cell lines maintain proliferation while expressing HIF-1α protein has been a subject of investigation and did not seem to correlate with levels of HIF-1α, p21, or p27 levels (44). Previous studies have suggested that HIF-2α may promote cellular proliferation, with the relative balance between HIF-2α and HIF-1α determining the response to hypoxia (48).…”
Section: (D and E) Mouse Mefs Frommentioning
confidence: 99%
“…Indeed, this phenomenon was not observed in the majority of tumor cells [32,39]. Besides, it is not clear that p27 is necessary to induce hypoxia-induced cell cycle arrest [6,21].…”
mentioning
confidence: 96%
“…Notably, the upregulation of cyclins inhibitors, such as p21 and p27, are reported [17,22,20]. However, some authors showed that the action of HiF-1α on p27 is not so clear since the expression of p27 under hypoxia may be independent of HiF-1α [6,9].…”
mentioning
confidence: 99%